Phase 3 Trials of Solanezumab for Mild-to-Moderate Alzheimer's Disease - Doody, Rachelle S; Thomas, Ronald G; Farlow, Martin; Iwatsubo, Takeshi; Vellas, Bruno; Joffe, Steven; Kieburtz, Karl; Raman, Rema; Sun, Xiaoying; Aisen, Paul S; Siemers, Eric; Liu-Seifert, Hong; et al. (The New England journal of medicine, 2014)
In two phase 3 placebo-controlled, randomized trials in 1012 and 1040 patients with mild-to-moderate Alzheimer's disease, solanezumab, a humanized monoclonal antibody that preferentially binds soluble forms of amyloid, did not improve cognition or functional status. Alzheimer's disease is associated with the accumulation of aggregated amyloid-beta (Aβ) peptide in the cerebral cortex and hippocampus. One approach to reducing brain amyloid involves increasing the clearance of Aβ by means of prolonged treatment with monoclonal antibodies directed against this peptide. In preclinical studies, a murine antibody that targeted the central domain of Aβ and was selective for soluble forms slowed Aβ deposition in a transgenic mouse model 1 ; in another transgenic murine model, Aβ–antibody complexes were present in the cerebrospinal fluid (CSF) and plasma, and behavioral deficits were reversed without a decrease in amyloid plaques, as assessed by . . .